TRANSFORMASI PENDIDIKAN ISLAM BERBASIS MASJID : PEMBERDAYAAN KOMUNITAS INDUSTRI DI MASJID JAMI' MANYAR - Sifrotul Maftuhah; M. Muizzuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the transformation of mosque-based Islamic education in empowering industrial communities with a case study at the YATAMAM Mosque in Manyar, Gresik. The study uses a qualitative approach with a case study method. Data collection was conducted through in-depth interviews, observations, and documentation of mosque administrators and the surrounding community. The results show that the YATAMAM Mosque has undergone a transformation in function from a center for ritual worship to a center for integrative Islamic education that includes religious education, formal education, economic empowerment, and community-based social services. This transformation is relevant to Jack Mezirow's Transformative Learning theory, which emphasizes changes in community awareness and perspectives through religious reflection and social praxis. In addition, the research findings are also in line with Azyumardi Azra's ideas on Islamic education reform, which emphasize the integration of Islamic traditions with modernity and social needs. From a community development perspective, mosques play a role as agents of community empowerment through partnerships with industry and the strengthening of the congregation's economy. The novelty of this research lies in the findings of a mosque-based Islamic education transformation model that integrates religious education, industrial waste management, and modern institutional governance into a single mosque ecosystem in an industrial area. The implications of this transformation contribute to strengthening the religiosity, economic independence, and social participation of industrial communities, thereby supporting the realization of a civil society. This research confirms that mosques have strategic potential as centers for Islamic education transformation in the context of industrialization. Keywords: Islamic education, mosque, transformation, Mezirow theory, community empowerment. This study aims to analyze the transformation of mosque-based Islamic education in empowering industrial communities with a case study at the YATAMAM Mosque in Manyar, Gresik. The study uses a qualitative approach with a case study method. Data collection was conducted through in-depth interviews, observations, and documentation of mosque administrators and the surrounding community. The results show that the YATAMAM Mosque has undergone a transformation in function from a center for ritual worship to a center for integrative Islamic education that includes religious education, formal education, economic empowerment, and community-based social services. This transformation is relevant to Jack Mezirow's Transformative Learning theory, which emphasizes changes in community awareness and perspectives through religious reflection and social praxis. In addition, the research findings are also in line with Azyumardi Azra's ideas on Islamic education reform, which emphasize the integration of Islamic traditions with modernity and social needs. From a community development perspective, mosques play a role as agents of community empowerment through partnerships with industry and the strengthening of the congregation's economy. The novelty of this research lies in the findings of a mosque-based Islamic education transformation model that integrates religious education, industrial waste management, and modern institutional governance into a single mosque ecosystem in an industrial area. The implications of this transformation contribute to strengthening the religiosity, economic independence, and social participation of industrial communities, thereby supporting the realization of a civil society. This research confirms that mosques have strategic potential as centers for Islamic education transformation in the context of industrialization. Keywords: Islamic education, mosque, transformation, Mezirow theory, community empowerment.